Clinical analysis and literature review of a complicated superior mesenteric artery stenosis with intestinal necrosis: A case report. Issue 17 (28th April 2023) - Zhou, Binbin; Huang, Junjie; Chen, Xiaobin; Lin, Chen; Xia, Yin; Jiang, Rong
Abstract : Rationale: Superior mesenteric artery (SMA) stenosis, as a common arterial disease, if coexists with other possible causes of abdominal pain, is complicated, which may require not only conservative treatment but also surgical intervention. Patient concerns: A 64-year-old male patient who was admitted to our hospital with pain located around the umbilicus and right lower quadrant for 12 hours. Diagnosis: SMA stenosis was initially diagnosed. After balloon dilatation of SMA and stent implantation, computed tomography angiography reexamination showed that the stent was migrated and the stenosis reoccurred. During the ileocecal resection and enterolysis, the necrotic bowel was found and cut open, and the intestinal fistula was found. Combined with his abdominal surgery history, the patient was diagnosed with complicated SMA stenosis with intestinal necrosis. Interventions: The balloon dilatation of SMA and stent implantation was performed. Because the stent was migrated and the stenosis reoccurred, so a balloon stent was implanted in the proximal stenosis of SMA again. The patient's symptoms were relieved and reoccurred again. The ileocecal resection and enterolysis were performed. Outcomes: The computed tomography angiography showed that the stents were well deployed and unobstructed after 9 months follow-up. Lessons: When dealing with undetermined abdominal pain that especially has something to do with mesenteric artery ischemia, if there coexists with other possible causes of abdominal pain, we cannot only focus on vascular diseases. We should be vigilant, integrate multiple factors and their interactions to guarantee the accuracy and timeliness of diagnosis and therapy.